"Bounce at the Bell": a novel program of short bouts of exercise improves proximal femur bone mass in early pubertal children. Issue 8 (25th July 2005) - McKay, H A; MacLean, L; Petit, M; MacKelvie-O'Brien, K; Janssen, P; Beck, T; Khan, K M
Abstract : Objectives: To examine the effects of a simple and inexpensive physical activity intervention on change in bone mass and structure in school aged children. Methods: Fifty one children (n = 23 boys and 28 girls; mean age 10.1 years) participated in "Bounce at the Bell" which consisted of 10 counter-movement jumps 3× per day (total ∼3 min/day). Controls were 71 matched children who followed usual school practice. We assessed dietary calcium, physical activity, physical performance, and anthropometry in September and after 8 months of intervention (June). We measured bone mineral content (BMC) and bone area at the lumbar spine, total body, and proximal femur. Proximal femur scans were also analysed for bone geometry and structural strength using the hip structural analysis program. Lean and fat mass (g) were also calculated. Results: Groups were similar at baseline and did not differ in weight, height, total body, lumbar spine, proximal femur, or femoral neck BMC. Control children had a greater increase in adjusted total body BMC (1.4%). Intervention children gained significantly more BMC at the total proximal femur (2%) and the intertrochanteric region (27%). Change in bone structural parameters did not differ between groups. Conclusions: This novel, easily implemented exercise program, took only a few minutes each day and enhanced bone mass at the weight bearing proximal femur in early pubertal children. A large, randomised study of boys and girls should be undertaken powered to test the effectiveness of Bounce at the Bell in children at different stages of maturity, and in boys and girls independently.